SEARCH FOR HIGH-ENERGY MUON NEUTRINOS FROM THE "NAKED-EYE" GRB 080319B WITH THE IceCube NEUTRINO TELESCOPE - Abbasi, R; Abdou, Y; Abu-Zayyad, T; Adams, J; Aguilar, J; Ahlers, M; Andeen, K; Auffenberg, J; Bai, X; Baker, M; Barwick, S; Bay, R; et al. (Institute of Physics Publishing, 2009)
We report on a search with the IceCube detector for high-energy muon neutrinos from GRB080319B, one of the brightest gamma-ray bursts (GRBs) ever observed. The fireball model predicts that a mean of 0.1 events should be detected by IceCube for a bulk Lorentz boost of the jet of 300. In both the direct on-time window of 66s and an extended window of about 300s around the GRB, no excess was found above background. The 90% CL upper limit on the number of track-like events from the GRB is 2.7, corresponding to a muon neutrino fluence limit of 9.5 × 10-3 erg cm-2 in the energy range between 120 TeV and 2.2 PeV, which contains 90% of the expected events. © 2009 The American Astronomical Society. All rights reserved.